Effect of Courtyard Aspect Ratio on Annual Cooling Energy of Highrise Apartment in Surabaya - Dewi, Putri Melati; Antaryama, I Gusti Ngurah; Defiana, Ima (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2020)
Rapid development of high-rise apartments, which rely on mechanical cooling,would increase energy consumption. Courtyard existed in various geometries of ahigh-rise apartment in Surabaya as a result of useful layout configuration. The court-yard is one of the passive cooling strategies in vernacular building and is reportedto reduce a building’s energy consumption. The size of the courtyard affects the per-formance of the courtyard. In high-rise courtyard apartments in Surabaya, there isa wide variation of building width and length, affecting the courtyard aspect ratio.This paper investigates the result of annual cooling energy of different courtyardaspect ratio on five apartment geometries with courtyard: H Geometry, U Geom-etry, Double U Geometry, Double L Geometry, and Quadruple L Geometry. Themethod of this research is experimental research with simulation as a tactic. Design-Builder by EnergyPlus is used as simulation tools in this research. The result revealsthat a courtyard with an aspect ratio of 1:2 tends to perform better than a squarecourtyard. Elongating the courtyard of H and U Geometry would reduce the annualcooling energy in all orientations. Elongating the courtyard of Double U, Double L,and Quadruple L Geometries would reduce the annual cooling energy in northwest-southeast orientation and increase annual cooling energy if the building is elongatedalongside the northeast axis..